A life journal into the future: Development of a storytelling approach for establishing career identity and agency in career counselling. Issue 6 (2nd November 2019) - Yang, Peter
ABSTRACT: This paper describes a creative approach to implementing career counselling and guidance in contemporary higher education. Following a theoretical discussion on the motivational mechanism underlying the career exploration process, the validity of using a storytelling approach to establish undergraduate students' career identity was examined. A Life Journal into the Future was then finalised, linking career exploration and career management. Methodologically, the career writings of 128 students were examined through a template analysis, which was established by a conceptualisation of 132 participants' ideal careers. The results showed that undergraduates' low awareness of personal strengths and lack of motivation for pursuing careers could be mitigated through construction of career identity, career writing and the holistic narrative constitution of a prospective career story.